Cryostat Slice Irregularities May Introduce Bias in Tissue Thickness Estimation: Relevance for Cell Counting Methods. (15th July 2015) - Puigdellívol-Sánchez, Anna; Giralt, Albert; Casanovas, Anna; Alberch, Jordi; Prats-Galino, Alberto
Abstract: Stereological techniques using the optical disectors require estimation of final section thickness, but frozen tissue irregularities may interfere with this estimation. Cryostat slices from rodent nerve tissues (dorsal root ganglia, spinal cord, and brain), cut at 16, 40, and 50 μ m, were digitized with a confocal microscope and visualized through 3D software. Geometric section thickness of tissue ( T geom ) was defined as tissue volume/area. Maximal section thicknesses ( T max ), from the top to the bottom of the section, were measured in a random sample of vertical ZX planes. Irregularities were mostly related to blood vessels traversing the tissue and neuronal somas protruding over the cut surfaces, with other neuron profiles showing a fragmented appearance. Irregularities contributed to increasing the distance between the tops and bottoms of slices sectioned in different laboratories. Significant differences were found between T max and T geom for all thickness studies and counting frames ( p <0.01). The T geom / T max average rate was 68.4–85.7% in volumes around cell profiles (∼600–1, 200 μ m 2 ) and 83.3–91.8% in subcellular samples (∼25–160 μ m 2 ). Confocal microscopy may help to assess tissue irregularities, which might lead to an overestimation of tissue volume if section thickness is estimated by focusing on the top and bottom of the sections.